Pay for Women with Kids in Russia: Is There Any Discrimination? - Татьяна Сергеевна Карабчук; Варвара Львовна Панкратова (Journal of Economic Sociology, 2013)
The paper gives a review of the existing theories and empirical research devoted to the determinants of wage differences for mothers and non-mothers. The paper is aimed at discussing the advantages and disadvantages of the theoretical approaches in explanation of the mother wage penalty in Russia and other countries. The authors try to explain the wage gap by using three theoretical concepts: human capital theory, theory for compensating differences, and discrimination theory. Relying on the previous research results the authors conclude that wage discrimination does exist for mothers in Russia as well as in other countries like Germany, the UK and the USA.